Una fondazione, un convegno: in margine a un inizio - Anzilotti, Carlo; Fagioli, Francesca; Fagioli, Marcella; Hinna, Alessandro; Longobardi, Ernesto (Il sogno della farfalla, 2023)
On the 18th and 19th November 2022, the international scientific congress “50 years of Death instinct and knowledge. The Human Birth Theory and its implications” organized by Massimo Fagioli Foundation, has taken place in the Olympic Theatre in Rome. Many Italian and international scholars participated in the congress, proposing an open debate among psychiatrists, psychologists, psychotherapists, neonatologists and researchers from different fields (architecture, pedagogy, linguistics, art etc.) on topics such as diagnosis and cure of mental illness, psychotherapy and non conscious thought. This article aims to draw some conclusions on what discussed during the conference, focusing on future perspectives which will be at the core of the scientific and cultural research carried out by Massimo Fagioli Foundation.